Rapid Assessment of Strategic Purchasing in the Philippines: A Country Case Study - Vergil de Claro (ZBW - Leibniz Information Centre for Economics, 2018)
For many resource-constrained settings, challenges in financing mainly revolve around how to mobilize more resources for health, ensure that there is proper allocation of these resources, and use it as a leverage to shape provider behavior. In the Philippines, the state-run social health insurance is uniquely positioned to centralize health financing and can use this to shape the health market behavior. This is even more important, as the Philippines finally moves closer to its goal of universal coverage. The existing economic and political support offers a window of opportunity to create that leverage. Taking stock of the strengths and weaknesses of its current purchasing situation provides a strong basis for developing an action plan to enhance its health reform initiatives moving forward.
Keywords: 330; strategic purchasing; Philippines; PhilHealth; health financing